1999
DOI: 10.1007/s004250050614
|View full text |Cite
|
Sign up to set email alerts
|

Photoadaptation of two members of the Chlorophyta ( Scenedesmus and Chlorella ) in laboratory and outdoor cultures: changes in chlorophyll fluorescence quenching and the xanthophyll cycle

Abstract: The role of the xanthophyll cycle in the adaptation of two chlorococcal algae Scenedesmus quadricauda and Chlorella sorokiniana to high irradiance was studied under laboratory and outdoor conditions. We wished to elucidate whether the xanthophyll cycle plays a key role in dissipating the excesses of absorbed light, as in higher plants, and to characterise the relationship between chlorophyll fluorescence parameters and the content of xanthophyll-cycle pigments. The xanthophyll cycle was found to be operative i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 34 publications
5
51
2
1
Order By: Relevance
“…These devices present different characteristics according to the quality of actinic lamps (halogen, red or blue light emitted diodes), sensitivity and measuring units (cuvettes versus fiber). On the other hand, measurements of in vivo chlorophyll fluorescence in algal mass cultures in open or closed photobioreactors are still scarce (Vonshack et al, 1994;Torzillo et al, 1996;Masojídek et al, 1999Masojídek et al, , 2011Kromkamp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These devices present different characteristics according to the quality of actinic lamps (halogen, red or blue light emitted diodes), sensitivity and measuring units (cuvettes versus fiber). On the other hand, measurements of in vivo chlorophyll fluorescence in algal mass cultures in open or closed photobioreactors are still scarce (Vonshack et al, 1994;Torzillo et al, 1996;Masojídek et al, 1999Masojídek et al, , 2011Kromkamp et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of the xanthophyll cycle in microalgae is ambiguous, since its contribution to energy dissipation can vary significantly among species (Niyogi et al, 1997;Casper-Lindley & Bjo¨rkman, 1998;Masojidek et al, 1999;Masojidek et al, 2004). In this study, a distinct synthesis of zeaxanthin was observed in Haematococcus pluvialis cultures exposed to 400 mmol m À2 s…”
Section: Discussionmentioning
confidence: 60%
“…A linear relationship between zeaxanthin formation and NPQ has also been frequently observed in higher plants (Demmig-Adams & Adams, 1996). On the other hand, a number of reports show poor correlation between the lightinduced zeaxanthin accumulation and the quenching of variable chlorophyll fluorescence in higher plants (Lichtenthaler et al, 1992;Schindler & Lichtenthaler, 1994;Schindler & Lichtenthaler, 1996), as well as in green algae (Masojidek et al, 1999). Poor correlation has been also found in green algae Dunaliella, which has similar light-harvesting and xanthophyll-cycle pigments to that of higher plants (Casper-Lindley & Bjorkman, 1998).…”
Section: Ps I Ps Imentioning
confidence: 93%